PERAN SWITCHING COSTS TERHADAP KUALITAS LAYANAN DAN NIAT PEMBELIAN ULANG - Slamet Widodo; Akram Harmoni Wiardi (UNIB Press, 2019)
The objectives of the research is to confirm and test the relationship between service quality and repurchase intention moderated by switching costs. We conduct survey method to collect the primary data, the sample is the freight forwarding customer that staying in the Bengkulu province. The results of this study indicate that service quality has a positive relationship on repurchase intention in the context of freight forwarding services. The most dominant dimensions of service quality that has strong impact on customer repurchase intention are reliability, responsiveness, and assurance. Switching costs has a significant role to strengthen the relationship between service quality and repurchase intention. Customer that has a higher perception of switching costs would stay and continue to use the same freight forwarding services and recommend the services to the other people.